PARTISIPASI UMAT KRISTEN DALAM PENEGAKAN HUKUM - James, James (Jurnal Ilmiah Penegakan Hukum, 2015)
Indonesian nation is a country with law principle based, therefore all components availableinside. In automatically, is shall be oriented in law enforcement in practical in this case includingall Christian people in community of Indonesia, and encourage them to know it well, then invitethem at all to take participation when need to enforce the law around them. It is acknowledgedthat there are many things that can be done as loyal community in take participation all lawenforcement in nation, such as all people in community should obey the law in order, for neverbroke the laws and set away from legal practices. The importance things also every body isencouraged to contribute n many positively for the law may interact to social well and runsmoothly.